Preparation of monoclonal antibody against human KIAA0100 protein and Northern blot analysis of human KIAA0100 gene - He Cui; Xi Lan; Shemin Lu; Fujun Zhang; Wanggang Zhang (Journal of Pharmaceutical Analysis, 2017)
Monoclonal antibodies (MAbs) are important tools for the study of proteins′ function and structure. But there has been no report on the preparation of MAbs against human KIAA0100 protein up to date. Here, first, we generated the mouse MAb against human KIAA0100 protein using purified recombinant 6×Histidinc (6×His)-tagged human KIAA0100 protein segment (1557–2234) as an antigen; then, the mRNA expression of human KIAA0100 gene was detected in U937 cells using Northern blot analysis. The results showed that the mouse MAb against human KIAA0100 protein could sensitively recognize the human KIAA0100 protein using Western blot analysis and immunocytochemistry analysis. Besides, Western blot analysis revealed that human KIAA0100 gene possibly encoded two different protein products (254 kDa and <250 kDa) in U937 cells. Moreover, Northern blot analysis confirmed that human KIAA0100 gene might produced two different mRNA products (6000–10000 bp and 5000–6000 bp) in U937 cells. The results provide a basis for large-scale production of the MAb against human KIAA0100 protein, which will be useful for the study of human KIAA0100 protein′s function/structure and MAb-targeted drugs in the future.